D. Manuel de Portugal, leitor de Fr. Rodrigo de Deus, O.F.M - Fardilha, Luís de Sá (1997)
The introductory notes to the work Motivos Espirituaes (1st. edition, 1611) include two sonnets by Friar Agostinho da Cruz and one by D. Manuel de Portugal. These poems suggest that the text had been previously read and was, therefore, known by two authors. If it is no surprise that a Franciscan should know the work of another Franciscan, it is quite different in the case of a noble who is also a layman. First of all due to chronological reasons, but, most important of all, because this meant an adherence to some sort of spiritual model. It is quite clear that one sonnet alone does not express the spiritual models of its author, nor does it sustain the possibility of his acceptance of some of the spiritual principles suggested in the text written by Friar Rodrigo de Deus. In order to identify the context of this realtionship, we have also studied a small text printes in the last pages of the Obras by D. Manuel de Portugal (1st and only edition from 1605). This study helps to establish a more documented analysis of how this noble and layman accepted the principles enunciated by the author of Motivos Espirituaes. The aim of this study is, therefore, to examine the establisment of the criterion and circumstances which guided a personal and lay reading of a spiritual work largely disseminated during the 17th. century in Portugal.